1967
DOI: 10.1126/science.155.3762.575
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Exclusion: A Rapid Means for Inducing Homozygous Diploid Lines in Tetrahymena pyriformis , Syngen 1

Abstract: Genomic exclusion is an abnormal form of conjugation occurring between cells with defective micronuclei and normal cells with diploid micronuclei. The progeny are heterocaryons; each cell has an old macronucleus but a new diploid micronucleus derived from one meiotic product of the normal mate. Such cells express genes found in the old macronucleus, are sexually mature, and can be specifically selected. When inbred, they give rise to lines genetically homozygous at all known loci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(58 citation statements)
references
References 13 publications
1
57
0
Order By: Relevance
“…Round I genomic exclusion (1,8,21) is a special type of abortive mating between WT and star (*) strains which have defective, hypodiploid MICs. Star strains can form pairs with WT but are not able to produce pronuclei during nuclear exchange and fertilization stages of conjugation (18,50,78).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Round I genomic exclusion (1,8,21) is a special type of abortive mating between WT and star (*) strains which have defective, hypodiploid MICs. Star strains can form pairs with WT but are not able to produce pronuclei during nuclear exchange and fertilization stages of conjugation (18,50,78).…”
Section: Methodsmentioning
confidence: 99%
“…To clarify this issue, a WT MIC was reintroduced into the S134A rescued strain to create a "rejuvenated" strain. This is possible in Tetrahymena through round I genomic exclusion (1,8,21), a special type of abortive mating between WT and star (*) strains which have defective, hypodiploid MICs (see Materials and Methods for details). Since the S134A rescued cells stopped mating at meiosis II and did not produce pronuclei, they behaved like star cells, suggesting that they had defective MICs.…”
mentioning
confidence: 99%
“…Temperature-sensitive mutants blocked in cytokinesis have been collected (Frankel et al, 1976), and a general procedure for the selection of temperature-sensitive mutants has recently been outlined for Tetrahymena (Bruns & Sanford, 1978). The potential utility of Tetrahymena as a cell type for genetic analysis has increased dramatically with the exploitation of phenotypic assortment (Sonneborn, 1974) to produce functional heterokaryons (Bruns & Brussard, 1974a), genomic exclusion (Allen, 1967) to yield homozygotes in a matter of hours , and the microtitre technology for mass testing of clones (Orias & Bruns, 1976). The availability of a procedure for selection of mating mutants should be of value in coupling genetic and biochemical analyses to the sequence of events surrounding the development of the sexual pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Since progeny macronuclei are developmental derivatives of micronuclei following conjugation, schemes for mutagenesis must insert a mating between induction of mutations and selection for mutant phenotypes. In order to generate homozygotes for the expression of recessive mutations, the mating should be some form of self mating.The phenomenon of genomic exclusion has held great promise for mutagenesis since Allen (7,8) demonstrated that the first round of mating results in an induced self-fertilization; Fig. 1 outlines the events associated with the entire process.…”
mentioning
confidence: 99%
“…The phenomenon of genomic exclusion has held great promise for mutagenesis since Allen (7,8) demonstrated that the first round of mating results in an induced self-fertilization; Fig. 1 outlines the events associated with the entire process.…”
mentioning
confidence: 99%